MOTIVASI DARI KELUARGA DENGAN MINAT IBU MEMBERIKAN MPASI DINI AGAR TIDAK MENGHAMBAT TUMBUH KEMBANG BAYI: Motivation from the Family With the Mother's Interest in Providing Early Complementary Foods So as Not to Hamper the Baby's Growth and Development - Handianingsih, Ratih Tri Wahyu (LPPM - STIKES Pemkab Jombang, 2024)
One of the causes of nutritional problems in toddlers is the practice of early complementary feeding (MPASI). MPASI is additional food given to babies after the age of six months until the baby is 24 months old. Babies are ready to eat solid foods, both in growth and psychologically at the age of 6-9 months. So the role of the family is needed to prevent early complementary feeding. The purpose of this study was to analyze the relationship between family support and mothers' interest in giving early complementary foods in Kedung Galeng Village, Probolinggo City. This study used a correlational analysis design with a cross sectional approach. The sample data is a portion of families who have babies aged 0-6 months in the Kedung Galeng area in January 2022, a total of 71 families using a purposive random sampling technique. Data collection included coding, editing, and tabulating. Then the data were analyzed by computer with the Spearman test p value: 0.05. The results showed that 32 respondents (45.1%) gave high family support for Early MPASI, 36 respondents (50.7%) gave Early MPASI and p value: 0.000. The conclusion of the study is that there is a relationship between family support and the mother's interest in giving early complementary foods at Kedung Galeng (p = 0.000 <0.05). The suggestions put forward are that it is expected that midwives will improve counseling/education regarding exclusive breastfeeding and month-to-month complementary foods both in practice locations by making a commitment not to work with milk products for pregnant women, etc